Assessment of potential for participatory rangeland management to increase carbon sequestration - Ritchie, Mark; Sircely, Jason (International Livestock Research Institute, 2024)
Participatory Rangeland Management (PRM) (Flintan and Cullis 2010, Robinson et al. 2020) is an approach for supporting pastoralists in managing their rangelands according to their knowledge and interests. PRM has been piloted in Ethiopia, Kenya, and Tanzania and is now expanding elsewhere. Appropriate carbon finance would complement PRM by incentivizing improved management and rewarding pastoralists for carbon (C) they are already storing in rangeland ecosystems and increasing uptake of improved management and carbon sequestration. This study aimed to achieve two objectives: (1) Assess the potential for different PRM strategies to sequester CO2 in soil. (2) Assess the ability of a remote sensing method to measure livestock locations and impacts on vegetation, a critical set of variables in implementing PRM.